Pendampingan Perancangan Laporan Keuangan pada UMKM Big Bites - David Chandrawan; Ellynawati Ellynawati; Ratna Sari Dewi; Tuti Achyani; Yanti Apriyaningsih (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
Financial reports are an important tool for Micro, Small, and Medium Enterprises (MSMEs) in measuring their performance and financial health. This study aims to design a simple financial reporting system that can be implemented by Big Bites, a culinary business located in Bekasi City. The method used is a qualitative descriptive approach with stages of observation, interviews, and documentation during a three-month internship (October–December 2024). The results of the study indicate that before the design, Big Bites did not have a good financial recording system and still relied on manual records. Through the design of Microsoft Excel-based financial reports that include a general journal, ledger, trial balance, income statement, statement of changes in equity, and balance sheet, MSMEs can understand their financial condition more clearly and accurately. The implementation of this system is expected to assist MSMEs in business decision-making, financial planning, and increasing business credibility.